Energy of Wannier–Mott Exciton in Thin Film of Cadmium Telluride (CdTe) (Latakia University Journal -Basic Sciences Series, 2019)
In this work the effect of self-action potential charge carriers has been studied in heterogeneous compound consisted of three layers' system on Wannier –Mott Exciton, the binding energy formula for light and heavy exciton in CdTe thin film deposited on CdS substrate has been readied.Some Method approximations have been applied on light and heavy exciton binding energy ( ) Such as The Variational  Method and parabolic approximation for potential of holes. In this work has been illustrated the exciton roles conductivity current at the contact p-n in solar cells where the excitons have been decayed into free electrons and free holes.